Making more effective use of human behavioural science in conservation interventions. (September 2021) - Balmford, Andrew; Bradbury, Richard B.; Bauer, Jan M.; Broad, Steven; Burgess, Gayle; Burgman, Mark; Byerly, Hilary; Clayton, Susan; Espelosin, Dulce; Ferraro, Paul J.; Fisher, Brendan; Garnett, Emma E.; et al.
Abstract: Conservation is predominantly an exercise in trying to change human behaviour – whether that of consumers whose choices drive unsustainable resource use, of land managers clearing natural habitats, or of policymakers failing to deliver on environmental commitments. Yet conservation research and practice have made only limited use of recent advances in behavioural science, including more novel behaviour change interventions. Instead conservationists mostly still rely on traditional behaviour change interventions – education, regulation and material incentivisation – largely without applying recent insights from behavioural science about how to improve such approaches. This paper explores how behavioural science could be more widely and powerfully applied in biodiversity conservation. We consider the diverse cast of actors involved in conservation problems and the resulting breadth of behaviour change that conservationists might want to achieve. Drawing on health research, we present a catalogue of types of interventions for changing behaviour, considering both novel, standalone interventions and the enhancement of more traditional conservation interventions. We outline a framework for setting priorities among interventions based on their likely impact, using ideas developed for climate change mitigation. We caution that, despite its promise, behavioural science is not a silver bullet for conservation. The effects of interventions aimed at changing behaviour can be modest, temporary, and context-dependent in ways that are as-yet poorly understood. We therefore close with a call for interventions to be tested and the findings widely disseminated to enable researchers and practitioners to build a much-needed evidence base on the effectiveness and limitations of these tools.